Proceedings of China-Europe Conference on Geotechnical Engineering Volume 2 (Springer Series in Geomechanics and Geoengineering,, 2018)
This book compiles the second part of contributions to the China-Europe Conference on Geotechnical Engineering held 13.-16. August 2018 in Vienna, Austria. About 400 papers from 35 countries cover virtually all areas of geotechnical engineering and make this conference a truly international event. The contributions are grouped into thirteen special sessions and provide an overview of the geoengineering research and practice in China, Europe and the world: · Constitutive model · Micro-macro relationship · Numerical simulation · Laboratory testing · Geotechnical monitoring, instrumentation and field test · Foundation engineering · Underground construction · Environmental geotechnics · New geomaterials and ground improvement · Cold regions geotechnical engineering · Geohazards - risk assessment, mitigation and prevention · Unsaturated soils and energy geotechnics · Geotechnics in transportation, structural and hydraulic Engineering.